2015
DOI: 10.1002/app.43256
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of physisorbed silane on a silica particle surface treated with silane coupling agents by thermogravimetric analysis

Abstract: We investigated a new method for estimating the amount of silanes physisorbed on a silica particle surface treated with silane coupling agents from a weight loss curve measured by thermogravimetric (TG) analysis. The silica particles were treated with 3-glycidoxypropyl trimethoxysilane (GPTMS) or 3-mercaptopropyl trimethoxysilane (MrPTMS) with both dry and wet treatment methods. In the TG curve for silica particles treated with GPTMS, the weight decreased in three steps: 100-1708C (first step), 170-2508C (seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
2
29
0
1
Order By: Relevance
“…Overall, the TGA results here are consistent with reports on GLYMO‐TiO 2 , APTES‐SiO 2 , and other surface functionalized nanoparticles, in which three weight loss steps exist in the 25–500 °C range. Yamazaki et al attributed the three weight loss steps to physiosorbed monomeric silanes, physiosorbed polycondensated silanes, and chemisorbed silanes .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the TGA results here are consistent with reports on GLYMO‐TiO 2 , APTES‐SiO 2 , and other surface functionalized nanoparticles, in which three weight loss steps exist in the 25–500 °C range. Yamazaki et al attributed the three weight loss steps to physiosorbed monomeric silanes, physiosorbed polycondensated silanes, and chemisorbed silanes .…”
Section: Resultssupporting
confidence: 90%
“…Overall, the TGA results here are consistent with reports on GLYMO‐TiO 2 , APTES‐SiO 2 , and other surface functionalized nanoparticles, in which three weight loss steps exist in the 25–500 °C range. Yamazaki et al attributed the three weight loss steps to physiosorbed monomeric silanes, physiosorbed polycondensated silanes, and chemisorbed silanes . Salon et al indicated that compared to silane coupling agents with other functional groups, those based on amino groups exhibit fast polycondensation kinetics, hence the expected large second weight loss step .…”
Section: Resultsmentioning
confidence: 98%
“…Secondly, the nano‐silica showed small size and high surface energy, which was prone to aggregation, and thus leading to a significant decrease of the processing performance and reinforcing properties when it was used to rubber reinforcement. So far, researchers had proposed some surface modification methods, including surfactant modification, silane coupling agent modification, graft polymer modification and so on, to improve the dispersion of silica and the compatibility in the polymer matrix. These methods played a good role in improving the reinforcing properties of silica.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current research works focused on the choice of appropriate modifier and modification processes . There were few studies on the mechanism of silica ‐ reinforced rubber, such as Payne effect mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…2 In general, unreacted organic compounds for surface coating are then removed from a slurry by washing. Several analytical techniques are applied to evaluate metal oxide nanoparticles modified with organic compounds, which amounts to thermogravimetric (TG) analysis of the weight of organic coatings [3][4][5] and diffuse reflectance infrared Fourier transform (DRIFT) spectroscopy for the analysis of interactions between organic compounds and metal oxides. [5][6][7][8] On the other hand, information directly obtained from slurries, such as viscosity of a slurry 9 and the diameter of particles, 10 is limited at present.…”
Section: Introductionmentioning
confidence: 99%